Politeness Strategies Employed by the Trainers in Room Division Department BAPEPAR Nusa Dua - Wiadnyana Putri, I Gusti Ayu Vina (Lingual Journal of Language and Culture, 2017)
This article tries to analyze and discuss the politeness strategies employed by the trainers in room division department when they practice on the job training in the hotel. Politeness strategy was needed when the trainers serve the guest. This research was done by observation and interview with the trainer and the guest about their conversation. The analysis of politeness strategies that employed by the trainer focused on two discussions; (1) the kinds of politeness strategies used by trainer in room division department, and (2) the implications of politeness strategies used by trainer in room division department. This research used the theory from Brown & Levinson (1987) in his book entitled Politeness: Some Universals in Language Usages. The theory is supported by other theories that are considered relevant to the topic of discussion in this research. Based on the analysis, it was found that there were two kinds of politeness stratgies that employed by the trainer in room division department Bapepar Nusa Dua, they were positive face and negative face. Beside that, there are three implications by using politness strategies such as: respect behaviour, togheterness, and cooperative interaction. Keywords: Politeness strategies, trainer, guest